2017
DOI: 10.1590/s0100-736x2017001100001
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility patterns of Brazilian Haemophilus parasuis field isolates

Abstract: Haemophilus parasuis is the etiological agent of Glässer’s disease (GD), an ubiquitous infection of swine characterized by systemic fibrinous polyserositis, polyarthritis and meningitis. Intensive use of antimicrobial agents in swine husbandries during the last years triggered the development of antibiotic resistances in bacterial pathogens. Thus, regular susceptibility testing is crucial to ensure efficacy of different antimicrobial agents to this porcine pathogen. In this study, 50 clinical isolates from Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Six conventional male piglets (Large-White × Landrace) of 42 days of age, negative for H. parasuis [Microbiologically: upper respiratory tract free of H. parasuis confirmed by culturing on agar chocolate containing 64 μg/mL of bacitracin (Sigma-Aldrich, USA) as recommended by Miani, et al . 45 and PCR from swab using the primers HPS_219690793 as described by Howell, et al . 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Six conventional male piglets (Large-White × Landrace) of 42 days of age, negative for H. parasuis [Microbiologically: upper respiratory tract free of H. parasuis confirmed by culturing on agar chocolate containing 64 μg/mL of bacitracin (Sigma-Aldrich, USA) as recommended by Miani, et al . 45 and PCR from swab using the primers HPS_219690793 as described by Howell, et al . 3 .…”
Section: Methodsmentioning
confidence: 99%
“…(2015) showed cross-resistance between Tiamulin and Valnemulin, observed as well between Lincomycin and Tylosin Pringle et al., 2004 . These evidences need to be carefully interpreted in our particular case; in 2017 we demonstrated the circulation of G. parasuis clinical isolates highly resistant to Lincomycin, Tiamulin and Tylosin Miani et al., 2017 . Although the cross-resistance between macrolides would be a logical explanation for understanding the presence of resistant strains to Tildipirosin in Brazil, further studies need to be done to investigate the evolutionary process of G. parasuis resistance to Tildipirosin in regions with high resistance to Lincomycin.…”
mentioning
confidence: 93%
“…As an evolutionary mechanism, microorganism can also develop cross-resistances between macrolides and lincosamides ( Roberts, 2008 ), possibly by plasmids carrying lnu(C) inactivanting gene of Lincosamyn ( Chen et al., 2010 ), raising a warning light on these two antimicrobial classes. In a previous study, we demonstrated a concern about the resistance trend of G. parasuis field strains to Tylosin Miani et al., 2017 . Here, we evaluated the in vitro efficacy of Tildipirosin, a semi‐synthetic derivative of the naturally occurring 16‐membered macrolide Tylosin on clinical isolates of G. parasuis .…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…For Brazilian strains, a study showed that field isolates were highly resistant to gentamicin, bacitracin, lincomycin and tiamulin, but sensitive to ampicillin, clindamycin, neomycin, penicillin, danofloxacin and enrofloxacin. However, a susceptibility test prior to antibiotic therapy during GD outbreaks should be considered by veterinarians (Miani et al 2017). Particularly for population-level prophylaxis, the emphasis should be on vaccination strategies to prevent systemic infection and mortality combined with good biosecurity practices (Aragon et al 2012, Luning et al 2015.…”
mentioning
confidence: 99%